2022
DOI: 10.1021/acs.joc.2c00382
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-Tetrazolyl-Substituted 3,4-Dihydroquinazoline Derivatives with Anticancer Activity via a One-Pot Sequential Ugi-Azide/Palladium-Catalyzed Azide-Isocyanide Cross-Coupling/Cyclization Reaction

Abstract: A new one-pot preparation of 4-tetrazolyl-3,4-dihydroquinazolines has been reported. The Ugi-azide reactions of 2-azidobenzaldehydes, amines, trimethylsilyl azide, and isocyanides produced azide intermediates without separation, which were treated with isocyanides to give 4-tetrazolyl-3,4-dihydroquinazoline derivatives through a sequential Palladium-catalyzed azide-isocyanide cross-coupling/cyclization reaction in moderate to good yields. The biological evaluation demonstrated that compound 6c inhibited breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In a very recent publication, Xiong et al [ 132 ] reported the synthesis of 4-tetrazolyl-3,4-dihydroquinazoline derivatives through a sequential Palladium-catalyzed azide-isocyanide cross-coupling/cyclization Ugi reaction, with good yields. The Ugi-azide reactions of various 2-azidobenzaldehydes (R 1 = 4-F, 4-Cl, 4-CH 3 O and 5-Me), amines (R 2 = Ph, 4-Cl-Ph, 4-Br-Ph, 4-CH 3 -Ph, 4-CH 3 O-Ph, 2-Cl-Ph, 2,4-dimethyl-Ph, n -Bu, i -Pr, t -Bu), trimethylsilyl azide and isocyanides (R 3 = t -Bu, c -C 6 H 11 , 1-adamantyl, n -Bu) produced azide intermediates that were treated with diverse isocyanides (R 4 = t -Bu, c -C 6 H 11 , 1-adamantyl, 4-CH 3 O-Ph, 4-Cl-Ph, MeO 2 CCH 2 , TsCH 2 ) to afford compound 18 examples of dihydroquinazoline derivatives ( Scheme 14 ).…”
Section: Anticancer Compounds Obtained From Mcrs Approachesmentioning
confidence: 99%
“…In a very recent publication, Xiong et al [ 132 ] reported the synthesis of 4-tetrazolyl-3,4-dihydroquinazoline derivatives through a sequential Palladium-catalyzed azide-isocyanide cross-coupling/cyclization Ugi reaction, with good yields. The Ugi-azide reactions of various 2-azidobenzaldehydes (R 1 = 4-F, 4-Cl, 4-CH 3 O and 5-Me), amines (R 2 = Ph, 4-Cl-Ph, 4-Br-Ph, 4-CH 3 -Ph, 4-CH 3 O-Ph, 2-Cl-Ph, 2,4-dimethyl-Ph, n -Bu, i -Pr, t -Bu), trimethylsilyl azide and isocyanides (R 3 = t -Bu, c -C 6 H 11 , 1-adamantyl, n -Bu) produced azide intermediates that were treated with diverse isocyanides (R 4 = t -Bu, c -C 6 H 11 , 1-adamantyl, 4-CH 3 O-Ph, 4-Cl-Ph, MeO 2 CCH 2 , TsCH 2 ) to afford compound 18 examples of dihydroquinazoline derivatives ( Scheme 14 ).…”
Section: Anticancer Compounds Obtained From Mcrs Approachesmentioning
confidence: 99%
“…Compound 108 was recognized as an efficient anti-breast cancer cell agent via broad biological investigations ( Scheme 22 ). 186 …”
Section: C–n Cross-coupling Reactions In Pharmaceutical Compoundsmentioning
confidence: 99%
“…Yao et al reported a new one-pot preparation of 4-tetrazolyl-3,4-dihydro quinazolines 96 using two types of azides, which participated in the Ugi reaction/sequential cyclization separately. 74 The Ugi-azide reactions of 2-azidobenzaldehydes 97 , amines, trimethylsilyl azide, and isocyanides form azide intermediates 98 without any separation process. These intermediates were then subjected to a sequential palladium-catalyzed azide–isocyanide cross-coupling and cyclization reaction with isocyanides, leading to the synthesis of 4-tetrazolyl-3,4-dihydroquinazoline derivatives 96 in moderate to good yields (Scheme 41).…”
Section: Multicomponent Reactions Of Azides To Construct Tetrazolesmentioning
confidence: 99%